New intertidal crickets from Comoros and Mascarene islands (Orthoptera: Trigonidiidae: Nemobiinae: Burcini) - Hugel, Sylvain; Desutter-Grandcolas, Laure (Zootaxa, 2021)
Nemobiinae crickets of the tribe Burcini Gorochov, 1986 are described for the first time from the shores of South Western Indian Ocean islands. The new genus Makalapobius n. gen. is proposed to include M. aigrettensis n. gen. n. sp. from Mauritius and M. masihu n. gen. n. sp. from Grande Comore, and the new genus Gabusibius n. gen. to include G. ndzilu n. gen. n. sp. from Anjouan, G. mosi n. gen. n. sp., from Mohéli, and G. dzindzanu n. gen. n. sp. from Mayotte. The species Speonemobius littoreus Vannini & Chelazzi, 1978 from Somalia coast is tentatively placed in the genus Gabusibius n. gen. as G. ? litoreus (Vannini & Chelazzi, 1978) n. gen. n. comb. The songs of G. mosi n. gen. n. sp. and M. aigrettensis n. gen. n. sp. are described. The threats to SWIO Burcini and endemism of Orthoptera from SWIO coastal areas are discussed.